Annotation algebras for RDFS - Buneman, P; Kostylev, E (CEUR Workshop Proceedings, 2010)
Provenance and annotation are intimately connected. On the one hand provenance can be regarded as a form of annotation, on the other hand, in order to understand how to convey annotations from source data to derived data, we need an account of how the data was derived - its provenance. Following a successful line of database research in which elements of a database are annotated with algebraic terms that describe the provenance of those elements, we develop an algebra of annotations for RDFS that differs from that developed for relational databases. We show how such an annotation algebra can be used for computing annotations on inferred triples that provide information on belief, trust and temporal aspects of data as well as providing a framework for default reasoning.